Differences in the response to TNF inhibitors at distinct joint locations in patients with psoriatic arthritis: results from nine European registries - Adrian Ciurea; Seraphina Kissling; Andrea Götschi; Lykke Midtbøll Ørnbjerg; Simon Horskjær Rasmussen; Bálint Tamási; Burkhard Möller; Michael J. Nissen; Bente Glintborg; Anne Gitte Loft; Almut Scherer; René Bräm; et al. (Arthritis Research & Therapy)
Abstract Background Efficacy of tumour necrosis factor inhibitors (TNFi) for peripheral arthritis in patients with psoriatic arthritis (PsA) has been established in randomized clinical trials that have used improvement in summated joint counts as an outcome. Whether joints at different anatomical locations might respond differentially to TNFi remains unknown. The aim of the study was to investigate potential variations in the responsiveness to a first tumour necrosis factor inhibitor (TNFi) among joints at distinct locations in patients with psoriatic arthritis (PsA) treated in routine clinical care. Methods Bionaive PsA patients from nine European countries were included in this observational cohort study if ≥ 1 joint was swollen at the initiation of a first TNFi as monotherapy or added to methotrexate. Only the 28-joint count was available without imaging data confirming the presence of synovitis. The primary outcome was time to first resolution of joint swelling at each joint level. Hazard ratios (HR) for resolution comparing different joint locations were estimated using interval-censored mixed-effects Cox proportional hazards models, including a random effect for country and patient, adjusted for age and sex. Results A total of 1729 patients with 8397 swollen joints at the start of TNFi were included. Considering the upper extremity, a higher rate of resolution of joint swelling (HR, 95% CI) was observed for the shoulder (1.65, 1.16–2.35) and elbow (1.90, 1.38–2.61), while a lower rate was found for the wrist (0.72, 0.62–0.83) compared to the joints of digit 3. Within fingers, and using the same reference, joint swelling resolved fastest in digit 4 (1.77, 1.49–2.11) and digit 5 (1.88, 1.53–2.31). A lower rate of resolution of joint swelling was found for the knee in comparison to the elbow, the corresponding joint on the upper limb (0.56, 0.40–0.78). Conclusion The time to resolution of joint swelling upon treatment with TNFi in patients with PsA seems to depend on the localisation of the affected joints.